ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR KIMIA PADA MATERI STOIKIOMETRI KELAS X DI SMA NEGERI 1 MANOKWARI - Allo, Angelina Bubun; Azrun, Muhammad (Universitas Papua, Manokwari, Indonesia, 2023)
This research was conducted to explain the factors and factors of chemistry learning difficulties experienced by students in stoichiometry material. This type of qualitative phenomenological research was used in this research. The subjects of this research were 58 class X students of SMA Negeri I Manokwari. The strategy for collecting information in research is carried out using perceptions, meetings, surveys, and report studies. The examination of information from perceptions is completed illustratively, and the investigation of information from meetings and opinion polls is completed clearly and interpretively. The research results show that the causes of students' learning difficulties are caused by internal factors, including students' low numerical capacity, students' low understanding of interpreting material, students' low learning inspiration, and students' low insight. External factors include less conducive study time and less optimal use of the facilities provided by parents.